2020
DOI: 10.1007/s00784-020-03413-2
|View full text |Cite
|
Sign up to set email alerts
|

Is the oral cavity relevant in SARS-CoV-2 pandemic?

Abstract: Objectives Recent scientific evidences suggest a relevant role of the oral cavity in the transmission and pathogenicity of SARS-CoV-2. Methods A literature search was performed in PubMed, up to April 30, 2020, focusing on SARS-CoV-2, COVID-19, oral cavity, and antimicrobial agents. Results Oral viral load of SARS-CoV-2 has been associated with the severity of COVID-19, and thus, a reduction in the oral viral load could be associated with a decrease in the severity of the condition. Similarly, a decrease in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
222
0
38

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(262 citation statements)
references
References 54 publications
2
222
0
38
Order By: Relevance
“…We reported on the bioavailability of hesperidin (about 2 micromol/L in plasma after ingestion of 500 mL of juice [25]) and the cited article, showing that micromolar doses of hesperidin inhibit the main protease of the SARS virus [37]; this suggests that an infection-blocking effect could be approached or achieved, even with an increase in citrus fruits intake for a certain period, particularly when consumed with peel and albedo, richer in hesperidin than juice [24]. Furthermore, it is conceivable that a high dose of nutraceutical principles should be present during and after the intake in the oral cavity and in the digestive tract, thus providing a local impediment to virus entry and replication in these anatomic sites, which play a crucial role in the COVID-19 disease [9,122,123].…”
Section: Discussionmentioning
confidence: 99%
“…We reported on the bioavailability of hesperidin (about 2 micromol/L in plasma after ingestion of 500 mL of juice [25]) and the cited article, showing that micromolar doses of hesperidin inhibit the main protease of the SARS virus [37]; this suggests that an infection-blocking effect could be approached or achieved, even with an increase in citrus fruits intake for a certain period, particularly when consumed with peel and albedo, richer in hesperidin than juice [24]. Furthermore, it is conceivable that a high dose of nutraceutical principles should be present during and after the intake in the oral cavity and in the digestive tract, thus providing a local impediment to virus entry and replication in these anatomic sites, which play a crucial role in the COVID-19 disease [9,122,123].…”
Section: Discussionmentioning
confidence: 99%
“…Although recent evidence suggests a relevant role of the oral cavity and its mucosae in the transmission and in the pathogenicity of SARS-CoV-2, as the entrance to the body of the virus, its protective or aggravating element for the infection and progression of the virus is still controversial [ 28 ]. It has been demonstrated that there is an association between periodontitis and a higher risk of increased gravity of COVID-19 in periodontopathic patients [ 31 ]. Most of the individuals (65%) in our sample had more than 20 teeth and they used to go to the dentist for control visits, demonstrating the importance given to the oral health condition.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that reducing infective SARS-CoV-2 load in saliva could play a key role in reducing the risk of viral transmission. In addition to the general population, the risk of transmission from infective saliva aerosols generated during clinical procedures is of particular concern, including authors of a recent Cochrane review who urge researchers to conduct studies to understand the potential of anti-bacterial mouthwashes and sprays to protect healthcare professionals during aerosolgenerating procedures 5,6 . Therefore, an understanding of the potential of mouthwash use to reduce SARS-CoV-2 viral load and modulate the risk of transmission in professional and public settings is a pressing question to address.…”
Section: Introductionmentioning
confidence: 99%